THE INFLUENCE OF DIGITAL MARKETING ON PURCHASE DECISIONS WITH SOCIAL CURRENCY AS AN INTERVENING VARIABLE IN FAMILY UNIFORM PURCHASES IN SUMBAWA - Magfirah Aulia Ramdhani; Ria Alvina; Muhammad Fikri Anugrah; Agus Santoso (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The development of digital marketing and the ease of access to information have driven significant changes in consumer behavior toward fashion products, including the rising trend of purchasing family set apparel. This study aims to analyze the influence of digital marketing on family set purchase decisions in Sumbawa and to evaluate the role of social currency as a mediating variable. This study employed a quantitative approach, and the data were analyzed using PLS-SEM. The study population consisted of residents of Sumbawa District who had purchased family set products, with samples selected through non-probability purposive sampling. The findings indicate that digital marketing has a positive and significant effect on both purchase decisions and social currency. However, social currency shows a weak, insignificant effect on purchase decisions, functioning only as a partial mediator with limited mediating strength. Respondents in this study have the following characteristics, who tend to purchase products priced below Rp200,000 and prefer COD payment, reflecting cautious consumption patterns driven more by economic considerations.